Oxylipins in food and biological systems: from biosynthesis, distribution, and bioactivity to applications in food quality and safety - Shitong Wang; Weibo Lu; Lijun Ge; Huixiang Wu; Jiahui Wu; Keyun Cheng; Hailong Xiao; Xinyuan Wang; Funing Huang; Shiqi Wang; Kang Chen; Yunkai Wu; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Delayed and asymmetric groundwater responses to meteorological forcing across Germany revealed by lagged mutual information - Fangfei Cai; Funing Ma; Zhenxue Dai; Junjun Chen (Journal of Hydrology, 2026)

Autonomous inverse modeling of complex groundwater systems via a physics-integrated large language model multi-agent framework - Funing Ma; Junjun Chen; Zhenxue Dai; Fangfei Cai; Yingtao Hu (Water Research, 2026)

Chemical insights into marine lipid oxidation and its dual role in atherosclerosis: implications for food processing and functional food development - Jing Xue; Ziyang Hu; Hongjie Chen; Jiaqi Wang; Xiaoping Yang; Funing Huang; Shiqi Wang; Hailong Xiao; Jianjun Jiang; Xinyuan Wang; Keyun Cheng; Guofang Shen; et al. (Food Chemistry, 2026)

Impact of groundwater extraction intensity on the monitoring design for seawater intrusion in heterogeneous coastal aquifers - Funing Ma; Junjun Chen; Zhenxue Dai; Fangfei Cai; Dayong Wang; Yue Ma (Journal of Hydrology, 2025)

Micro/nano-plastics and microalgae in aquatic environment: Influence factor, interaction, and molecular mechanisms - Wenfeng Yang; Pan Gao; Zongda Ye; Funing Chen; Liandong Zhu (Science of The Total Environment, 2024)

Impact of reactive mineral facies distributions on radionuclide sorption properties in multiscale heterogeneous granite rocks - Wei Chen; Zhenxue Dai; Javier Samper; Hui Ling; Chuanjun Zhan; Funing Ma; Zhijie Yang; Xiaoying Zhang; Mohamad Reza Soltanian (Hydrogeology Journal, 2023)

Upscaling of Se(IV) sorption coefficients with hierarchical mineral characterization in multi-scale fractured granite - Funing Ma; Xiaoying Zhang; Chuanjun Zhan; Wei Chen; Linlin Qi; Zhenxue Dai (Stochastic Environmental Research and Risk Assessment, 2023)

Lessons from farmers’ adaptive practices to climate change in China: a systematic literature review - Jiao Chen; Funing Zhong; Dingqiang Sun (Environmental Science and Pollution Research, 2022)

In Vitro Inhibition of Acetylcholinesterase, Alphaglucosidase, and Xanthine Oxidase by Bacteria Extracts from Coral Reef in Hainan, South China Sea - Lin Tan; Suxia Guo; Funing Ma; Chen Chang; Isabel Gómez-Betancur (Journal of Marine Science and Engineering, 2018)
Acetylcholinesterase is one of the most important enzymes in living organisms, which is responsible for the synapse cholinergic and other nervous processes. However, its inhibiting effects have proven to have pharmacological applications in the treatment of different diseases, as well as in the control of insect pests; thus, the search for inhibitors is a matter of interest for biomedical and agrochemical fields. Alzheimer’s is a progressive neurodegenerative disease, which can be seen as a wide degeneration of synapses, as well as neurons, in the cerebral cortex, hippocampus, and subcortical structures. Acetylcholinesterase inhibition is an important target for the management of Alzheimer’s. Additionally, diabetes mellitus is a chronic disease with clinical manifestation of hyperglycemia, due to the ineffective production of insulin that controls the level of blood glucose. Alphaglucosidaseinhibitors could retard the uptake of dietary carbohydrates and have shown significant therapeutic effects in clinical application. Fifty-five ethyl acetate extracts from nine bacterial families from Hainan (China) were evaluated to observe their acetylcholinesterase, alphaglucosidase, and xanthine oxidase inhibitory activity. Moreover, a screening of inhibitory activity against the pathogens fungi Fusarium oxysporum and Colletotrichum gloeosporioides was performed. The best acetylcholinesterase and alphaglucosidase inhibitory activity was shown by Vibrio neocaledonicus (98.95%). This is the first report of inhibition of both enzymes by ethyl acetate extract from this strain.

Risk alleles for IgA nephropathy-associated SNPs conferred completely opposite effects to idiopathic membranous nephropathy in Chinese Han - Xiaosong Qin; Chen Wang; Guanting Lu; Mengle Peng; Guixue Cheng; Hongquan Zhu; Yun Cao; Jianhua Liu; Yuzhong Li; Hong Cai; Funing Yang; Yanhong Liu; et al. (Immunologic Research, 2017)